Career Paths in Educational Leadership: Examining Principals’ Narratives - Parylo, Oksana; Zepeda, Sally J.; Bengtson, Ed (Alberta Journal of Educational Research, 2013)
This qualitative study analyzes the career path narratives of active principals. Structural narrative analysis was supplemented with sociolinguistic theory and thematic narrative analysis to discern the similarities and differences, as well as the patterns in the language used by participating principals. Thematic analysis found four major themes in the narratives: (1) passion for teaching and education; (2) external motivation to become a principal; (3) importance of the experience as an assistant principal; and (4) recent changes in the principalship. While all of the participants acknowledged difficulties associated with the principalship, the findings revealed differences between male and female leaders’ narratives in terms of structure, content, and style as well as certain similarities. Cette étude qualitative analyse les récits de directeurs d’école intérimaires par rapport à leur cheminement professionnel. Nous avons eu recours à une analyse narrative structurale, complétée par la théorie sociolinguistique et une analyse narrative thématique, pour examiner les patrons, les similarités et les différences linguistiques chez les directeurs et les directrices qui ont participé. L’analyse thématique a identifié quatre thèmes majeurs dans les récits : (1) une passion pour l’enseignement et l’éducation; (2) une motivation externe à devenir directeur d’école; (3) l’importance de l’expérience de directeur adjoint; et (4) des changements récents dans le rôle de directeur. Tous les participants ont reconnu des difficultés liées au rôle de directeur d’école, mais la structure, le contenu et le style des récits des hommes étaient différents de ceux des femmes. Notons que tous les récits partagaient quand même certaines similarités.